Prevalence of traumatic dental injuries and associated factors among preschool children in Amman, Jordan. Issue 6 (2nd June 2015) - ElKarmi, Rawan Fawwaz; Hamdan, Mahmoud Anwar; Rajab, Lamis Darwish; Abu‐Ghazaleh, Suha Bassam; Sonbol, Hawazen Nizar
Abstract: Background/Aims: Dental trauma is a major public health problem. However, baseline data regarding traumatic injuries to primary teeth in Jordan are lacking. The study aimed at evaluating the prevalence of traumatic dental injuries to primary anterior teeth among preschool children in Amman (Jordan), investigating the relationship between dental trauma and associated factors, and assessing the treatment provided and treatment need. Materials and methods: After obtaining ethical approval and parental consent, a cross‐sectional population‐based study examined a total of 1198 children attending 39 preschools randomly selected from different areas of Amman. Chi‐square test and stepwise logistic regression modeling were used for statistical analysis. Results: The prevalence of traumatic dental injuries was 26.4%. The upper incisors were more likely to sustain dental trauma (91.7%). No statistically significant association was established between dental trauma and any of the socio‐demographic variables. The most common type of dental trauma was enamel fracture (43.1%) followed by pulp injury (39.7%). The odds ratio suggested that the risk of dental trauma was 1.89 times greater if the overjet was >3 mm, 1.93 times greater if the child had an anterior open bite, and 2.56 times greater if the child had inadequate lip coverage. Only 25.3% of children diagnosed with a TDI visited a dentist following their trauma. Conclusions: The prevalence of dental trauma among preschool children in Amman (Jordan) was high; therefore, it is highly recommended to plan campaigns targeting parents, children, and medical/dental care providers that stress the importance of preventing dental trauma and treating it promptly.